(untitled) (Communications in Computational Physics, 2014)
Plasma radiative properties play a pivotal role both in nuclear fusion and astrophysics. They are essential to analyze and explain experiments or observations and also in radiative-hydrodynamics simulations. Their computation requires the generation of large atomic databases and the calculation, by solving a set of rate equations, of a huge number of atomic level populations in wide ranges of plasma conditions. These facts make that, for example, radiative-hydrodynamics in-line simulations be almost infeasible. This has lead to develop analytical expressions based on the parametrization of radiative properties. However, most of them are accurate only for coronal or local thermodynamic equilibrium. In this work we present a code for the parametrization of plasma radiative properties of mono-component plasmas, in terms of plasma density and temperature, such as radiative power loss, the Planck and Rosseland mean opacities and the average ionization, which is valid for steady-state optically thin plasmas in wide ranges of plasma densities and temperatures. Furthermore, we also present some applications of this parametrization such as the analysis of the optical depth and radiative character of plasmas, the use to perform diagnostics of the electron temperature, the determination of mean radiative properties for multicomponent plasmas and the analysis of radiative cooling instabilities in some kind of experiments on high-energy density laboratory astrophysics. Finally, to ease the use of the code for the parametrization, this one has been integrated in a user interface and brief comments about it are presented.